An accelerated testing method for the evaluation of atmospheric corrosion resistance of weathering steels. Issue 2 (2nd March 2015) - Qian, Yuhai; Xu, Jingjun; Li, Meishuan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a laboratory accelerated periodic immersion wet/dry cyclic corrosion test, reflecting the alternate wet/dry process during the atmospheric exposure of metallic materials, which can be applied to evaluate the atmospheric corrosion resistance (ACR) of weathering steels in a very short period. Design/methodology/approach – This test method uses 0.01 M sodium bisulfite aqueous solution with pH 4.4 as the immersion medium, simulating the notable characteristics of sulfur dioxide pollutant in industrially polluted atmospheres. During the test process, the tested specimens are immersed into the solution for 12 minutes, immediately followed by the subsequent drying process for 48 minutes, and such alternate process consists of a cyclic period, i.e. 1 hour. As a result of this procedure, a relative corrosion rate is defined to determine the ACR. To determine a preferred test period, different test periods including 72 and 200 hours were compared. Findings – Compared with several other commonly used test methods, it was confirmed that the relative ACR of various steels can be determined after testing for only 72 hours. The constituent of the corrosion products, i.e. the rust layer, was consistent with that formed after long-term exposure in a typical outdoor atmospheric environment. Originality/value – The test method enables comparative testing for ranking the ACR of weathering steel during the development of new weathering steels.